المدح في الشعرالعربي لإسحاق نصر الدّين: دراسة تحليلية: A Critical Study of the Arabic Praise Poem of Ishaq Nasrudeen - Lawal, Rahman (SIBAWAYH Arabic Language and Education, 2023)
عنوان هذه الورقة  المدح فى شعرإسحاق نصر الدين: دراسة تحليلية. يعد إسحاق نصرالدين من الشعراء الذين لم يتخذوا من الشعر وسيلة للتكسب وبعد الإطلاع على ديوانه وجد الباحث أن له قصائد كثيرة في المدح مما جعله يعتمد على أنّه كان صادقا في مدحه وأن الممدوحين الذين نالوا من الشاعر هذه المدائح كانوا جديرين بالمدح، وفي هذا البحث تناول الباحث الثلاثة من قصائد حسن إسحاق نصر الدين ودرسهم دراسة نقدية. والمنهج المتبع هو المنهح التحليلي ويهدف الباحثإلي نقد الأساليب الفنية في القصائد وتوصل الباحث إلي أن الشاعر متميز في المدح.كلمات مفتاحية: النقد, الشعر, القرآن, العيوب, والقافيةAbstract The title of this paper is Praise in the Poetry of Ishaq Nasr al-Din: An Analytical Study. Ishaq Nasr al-Din is considered one of the poets who did not use poetry as a means of earning money. After reviewing his collections, the researcher found that he had many poems in praise, which made him rely on the fact that he was sincere in his praise and that the praised people who received these praises from the poet were worthy of praise. In this research, the researcher addressed The three poems of Hassan Ishaq Nasr al-Din and he studied them critically. The method followed is the analytical approach, and the researcher aims to criticize the artistic methods in the poems. The researcher concluded that the poet is distinguished in praise.Keywords: criticism, poetry, the Qur’an, flaws, and rhyme